We can't stop cooking. Investigating the enablers for the uptake of improved cookstoves in Benue State, Nigeria - Atagher, Peter Tyev (2019)
Improved cookstoves (ICS) are designed to cook more efficiently and cleanly: helping to reduce the drudgery associated with biomass fuel collection as well as to lower smoke emission and mitigate the health and environmental effects of household air pollution (HAP). HAP is linked to the emission of particulate matter and gases, such as nitrogen dioxide, sulphur dioxide, carbon dioxide, in addition to volatile organic compounds derived from solid biomass fuel smoke present in certain levels that have adverse health impacts. HAP is closely associated with disease outcomes such as respiratory infections, cataract and chronic obstructive pulmonary disease. It is estimated that firewood accounts for more than half the total energy used, mostly on open fires for cooking in Sub-Saharan Africa. Consequently, improved biomass cookstoves are promoted by international non-governmental organizations (NGOs) and local producers in this region in order to address these issues. However, uptake of such stoves still remains low. This study investigates end-user perspectives on cookstove and fuel use in Benue State, Nigeria, to better understand local cooking system choices. ‘Human-centered’ qualitative approaches including questionnaires, interviews, focus group discussions and field observations were employed to facilitate an understanding of household access to and availability of cooking fuels and stoves in Benue State, Nigeria. To contextualize the study and assist with questionnaire development, data on household fuel use from the Nigeria Demographic and Health Survey (NDHS) was analyzed. The key findings of this study indicate that the cost and availability of fuel determine users’ stove choices with most respondents demonstrating strong preference for using firewood on traditional stoves. ICS were often perceived as too small to satisfy households’ cooking needs: especially in the case of larger households and among ethnic groups where cooking large quantities of food is viewed as culturally important. Moreover, stove and fuel stacking were common, whereby ICS were used alongside traditional stoves deterring complete energy transitions. With regard to policy, the study suggests that fuel subsidies negatively impact households’ cooking activities while ICS initiatives receive limited financial support from the government. This research highlights the centrality of socio-cultural factors including gender relations to family fuel and stove choices. Ultimately, this study challenges policymakers to demonstrate their commitment towards stove development through financial support and enhanced gender-specific policies. Moreover, it encourages promoters of ICS to review stove designs in order to align them with the culture, needs and priorities of their end users.